Re-entry Policy Implementation Effectiveness: a Case of Secondary Schools in Lusaka, District, Zambia - Gift Muyunda (Research and Education Development (READ) Institute collaborate with Faculty of Education and Teacher Training of IAIN Palopo, 2021)
The overall purpose of this study was from an educational management perspective to explore the effectiveness of the re-entry policy implementation in public schools in Lusaka District, Zambia, and highlight the missing links between the stipulated re-entry policy of 1997 and the actual practice on the ground in terms of its implementation in secondary schools. This study was qualitative and employed a case study approach, and standard open-ended interviews were used to obtain data from the district education officers, headteachers, teachers, and parents to teen mothers. The study's findings imply that the re-entry policy implementation in the selected secondary schools is not practical to a high degree. The study findings further indicated that the policy is silent, and there is no awareness of the policy in secondary schools due to unclear policy goals and objectives. The study findings also indicated no sense of ownership of the policy by stakeholders responsible for implementing the policy. Further, the study concluded that secondary schools' policy implementation is not practical because there are no clear stated objectives, implementation and monitoring strategies, financial, human, and legal resources. Hence, this study recommended that the Ministry of General Education redesign the policy, including all stakeholders in the formulation process, and clearly state its goals and objectives to ensure future successful implementation.